189k views
5 votes
Solve for u.

4u²+3=-8u
If there is more than one solution, separate them with commas.
If there is no solution, click on "No solution."

User Ericslaw
by
4.8k points

1 Answer

4 votes

Answer:

u =
-(1)/(2) ; u =
-(3)/(2)

Explanation:

4u² + 3 = -8u

4u² + 3 + 8u = -8u + 8u (add 8u both sides)

4u² + 8u + 3 = 0 simplify

using quadratic equation:

- 8 ± √ (8² - 4 * 4 *3)

u = ------------------------------

2 * 4

u =
-(1)/(2) ; u =
-(3)/(2)

User David Khourshid
by
4.9k points